On the tradition of using hanging metal seals in the offices of the Golden Horde and Post-Horde States - Belyakov A.V. (Золотоордынское обозрение)
Research objectives: Following M.A. Usmanov stated claim that hanging seals were not at all used in the Horde offices, this became an indisputable fact. However, D. Kolodzeichik proved the existence of golden hanging seals, which were officially called altunbaisa, on Crimean charters of the 17th century. He suggested that this innovation was introduced into the office of the Gireys. Recent studies allow us to speak confidently about the widespread existence of gold and silver gilded seals in the territory of the Siberian, Crimean and Kazan Khanates, in the Nogai Horde, and in the Caucasus in the 16th century. In addition, they are recorded among the peoples of the Middle Volga and Trans-Urals. Only two types of documents were certified with such seals – wool and letters of commendation. Traces of the phenomenon lead to the late Golden Horde’s offices. This paper examines information about the use of metal hanging seals in the offices of the Golden Horde and post-Horde states. Research materials: Messages from the inventories of the archives of the Posolsky Prikaz and the Collegium of Foreign Affairs, Russian-Crimean and Russian-Nogai embassy books, as well as documents of the internal office work of the Foreign Ministry. Results and scientific novelty of the study: The existence of gold and silver hanging seals, which were used to fasten individual documents in the post-Horde states of the 16th century, is demonstrated. At the same time, indirect data and the logic of the transformation of clerical practices allow us to assume their presence at least as early as the 15th century. Golden seals, apparently, became a logical step in the gradual transformation of the khan’s labels and paiz. At some point, these two items merged into one. This could have happened after the practice of awarding paiz ceased. The observations made here allow us to rethink the ideas about the Horde’s stationery traditions that have been long established in the scientific community.